2016
DOI: 10.1007/s10792-016-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

Retina ganglion cell/inner plexiform layer and peripapillary nerve fiber layer thickness in patients with acromegaly

Abstract: Increased secretion of growth hormone and insulin-like growth factor-1 in acromegaly has various effects on multiple organs. However, the ocular effects of acromegaly have yet to be investigated in detail. The aim of the present study was to compare retina ganglion cell/inner plexiform layer (GCIPL) and peripapillary nerve fiber layer thickness (pRNFL) between patients with acromegaly and healthy control subjects using spectral domain optical coherence tomography (SD-OCT). This cross-sectional, comparative stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
2
1
1
Order By: Relevance
“…In contrast, Yazgan et al reported increment in RNFL thickness in each quadrant [6]. However, Şahin et al reported decreased RNFL thickness in inferotemporal and superotemporal quadrants [8]. In our study, there was a decrease in RNFL thickness in the inferior and superior quadrants.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…In contrast, Yazgan et al reported increment in RNFL thickness in each quadrant [6]. However, Şahin et al reported decreased RNFL thickness in inferotemporal and superotemporal quadrants [8]. In our study, there was a decrease in RNFL thickness in the inferior and superior quadrants.…”
Section: Discussioncontrasting
confidence: 90%
“…In addition, similar to the results in this study, when Duru et al examined the relationship between serum IGF-1 levels and RNFL thickness, they found no correlation [12]. Şahin et al reported an increase in GC-IPL thickness [8]. In the present study, GC-IPL thickness did not differ between the groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies have demonstrated that acromegalic patients with macroadenomas have decreased RNFL thickness due to chiasmal compression. ( 43–45 ) However, Yazgan and colleagues recently showed that acromegalic patients without macroadenomas have increased RNFL thickness, suggesting growth hormone excess has a protective effect on the neural retinal layers in the absence of compression. However, untreated growth hormone excess is an established risk factor of ON in FD/MAS, ( 11 ) which may be due to stretch/traction of the optic nerve in the setting of macrocephaly, or compression of the nerve or chiasm by expanded FD or macroadenomas, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Şahin и соавт. [42] обследовали 18 пациентов (33 глаза) с соматотропиномой гипофиза при помощи SD-OCT. Общая средняя толщина RNFL в перипапиллярной области у пациентов была меньше, чем в группе контроля (p = 0,01), более выраженное снижение толщины RNFL выявлено в верхневисочных и нижневисочных квадрантах. Толщина GCC сетчатки, включая внутренний плексиформный слой (GCIPL), во всех квадрантах внутреннего и внешнего колец по сетке ETDRS, за исключением центрального и нижневисочного квадрантов, у пациентов была меньше, чем в контроле (p < 0,05).…”
unclassified